Economic Dimensions of Mepe Kasur - Biati, Lilit; Mamlukhah, Mamlukhah; Munawir, Munawir; Ustanti, Mira (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The Mepe Kasur tradition of the Osing community in Kemiren Village, Banyuwangi, is more than a cultural ritual before Eid al-Adha; it embodies values of tolerance, harmony, and economic empowerment. The symbolic red-black (abang-cemeng) mattresses reflect protection from misfortune and household unity, while the collective practice of airing mattresses and the Tumpeng Sewu ritual strengthen social cohesion across generations. Beyond its spiritual meaning, Mepe Kasur has become a cultural attraction that contributes to the local economy through tourism, homestays, culinary experiences, and creative industries. This study employs a qualitative descriptive method with participatory observation, in-depth interviews, and literature review. The findings reveal that the Mepe Kasur tradition serves two main functions: first, as a means of cultural preservation that safeguards the identity and spiritual values of the Osing community; and second, as an effective social instrument for strengthening interfaith tolerance and promoting community-based economic growth. This tradition fosters social interaction across religions and generations while creating economic opportunities through tourism activities and local cultural products. Thus, Mepe Kasur not only sustains social harmony but also acts as a driving force for a sustainable culture-based economy within the Osing community.